Application of Formative and Supportive Propping as Innovation in the Cultural Practices of Growing Cacao - Moises Cansana Torrentira Jr. (Emerging Issues in Agricultural Sciences Vol. 6, 2023)
This chapter identified the stepwise procedures and the benefits of applying formative and supportive propping on cacao. Demand for cacao-based products is increasing, but the supply of these items is still insufficient in domestic and international markets. Due to its climate and favorable geographic location, the Philippines is suitable for cacao production and accessibility to both domestic and international trade. A demo farm was introduced with the innovative process using the stepwise methods of both formative and supportive propping. Observations were then recorded and analyzed. This study made use of a case study where two half hectares of land were used separately as demo farms. Case study [1] reveals a phenomenon peculiar to the study at hand like the application of innovation to an existing norm or practice. It was observed that given the right amount of fertilizer and performance of other cultural practices, formative propping can increase the production of cacao up to 40-50% per hectare per year. Additionally, with formative propping, the self-shading helps retain the moisture in the soil which can facilitate the activity of the microorganisms in the decomposition process. This will maintain the fertility of the soil which will then help the cacao tree nourish itself for the nutrition it needs for higher productivity. Increased cocoa pod production, decreased pruning activity, decreased soil evaporation through self-shading, maintained soil fertility through self-shading, production of healthy leaves, reduced weeding practises, maintained temperature beneath the canopy, and ease of performing other cultural practises in the cacao farm are some advantages of this innovation.